2020
DOI: 10.1073/pnas.1916828117
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of iodine in the stratosphere

Abstract: Oceanic emissions of iodine destroy ozone, modify oxidative capacity, and can form new particles in the troposphere. However, the impact of iodine in the stratosphere is highly uncertain due to the lack of previous quantitative measurements. Here, we report quantitative measurements of iodine monoxide radicals and particulate iodine (Iy,part) from aircraft in the stratosphere. These measurements support that 0.77 ± 0.10 parts per trillion by volume (pptv) total inorganic iodine (Iy) is injected to the stratosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
137
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(149 citation statements)
references
References 62 publications
12
137
0
Order By: Relevance
“…Another active iodine chemistry region is the tropical upper troposphere-lower stratosphere region (UTLS), where significant concentrations of iodine exist (Koenig et al, 2020) as a result of strong convection carrying iodine precursors emitted at the ocean surface (mainly CH 3 I). The effect of the new spectra on the J values in this region is similar to the effect at the surface, although the changes are less pronounced.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another active iodine chemistry region is the tropical upper troposphere-lower stratosphere region (UTLS), where significant concentrations of iodine exist (Koenig et al, 2020) as a result of strong convection carrying iodine precursors emitted at the ocean surface (mainly CH 3 I). The effect of the new spectra on the J values in this region is similar to the effect at the surface, although the changes are less pronounced.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Recent nitrate ion chemical ionization-atmospheric pressure interface-time-of-flight mass spectrometry (NO − 3 CI-API-ToF-MS) observations of IO − 3 -and IO 3 -containing ion clusters in coastal and polar environments, as well as complementary laboratory experiments in the absence of HO x , have been interpreted as direct measurements of gas-phase iodic acid (HOIO 2 , hereafter denoted as HIO 3 ) and HIO 3 clusters (Sipilä et al, 2016) by ionization of the ambient species by NO − 3 in the instrument inlet. Since all possible reaction paths for I, IO, and OIO with H 2 O are very endothermic (Canneaux et al, 2010;Hammaecher et al, 2011;Khanniche et al, 2017a) and IO x −H 2 O complexes are very weakly bound (Galvez et al, 2013), the formation of oxyacids may rather proceed via hydrolysis of higher iodine oxides (Kumar et al, 2018):…”
Section: Introductionmentioning
confidence: 99%
“…Currently, inorganic iodine emissions are considered to be the dominant sources contributing to the open ocean boundary layer iodine (Carpenter et al, 2013). A recent study by Koenig et al (2020) concluded that inorganic iodine sources play major role in comparison to the organic iodine sources in contributing even to the upper troposphere iodine budget. Laboratory investigations revealed that at the ocean surface, iodide (I -) dissolved in the seawater reacts with the deposited https://doi.org/10.5194/acp-2019-1052 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…However, in its vapor phase, it is a highly mobile gas which is toxic and easily spills into the air [ 10 ]. Recently, a paper about the quantitative detection of iodine in the stratosphere was reported wherein a link between air quality and ozone loss was established [ 11 ]. As the ozone destruction potential of iodine is 600 times more compared to that of chlorine, harmful effects of iodine are detrimental to the environment.…”
Section: Introductionmentioning
confidence: 99%